Therian origin of INSL3/RXFP2-driven testicular descent in mammals - Menzies, Brandon R.; Tarulli, Gerard A.; Frankenberg, Stephen R.; Pask, Andrew J. (Frontiers in Cell and Developmental Biology, 2024)
During early development in most male mammals the testes move from a position near the kidneys through the abdomen to eventually reside in the scrotum. The transabdominal phase of this migration is driven by insulin-like peptide 3 (INSL3) which stimulates growth of the gubernaculum, a key ligament connecting the testes with the abdominal wall. While all marsupials, except the marsupial mole (Notoryctes typhlops), have a scrotum and fully descended testes, it is unclear if INSL3 drives this process in marsupials especially given that marsupials have a different mechanism of scrotum determination and position relative to the phallus compared to eutherian mammals. To understand if INSL3 plays a role in marsupial testicular descent we have sequenced and curated the INSL3 gene and its receptor (RXFP2) in a range of marsupials representing every order. These data show a strong phylogenetic similarity between marsupial and eutherian orthologues, but not with monotreme INSL3s which were more similar to the ancestral RLN3 gene. We have also shown the genomic location of INSL3, and surrounding genes is conserved in a range of marsupials and eutherians. Furthermore, single cell RNA-seq and qPCR data show that INSL3 mRNA is expressed specifically in Leydig cells and expressed at higher levels during the testicular descent phase in a developing marsupial, the fat-tailed dunnart (Sminthopsis crassicaudata). Together, these data argue strongly for a therian origin of INSL3 mediated testicular descent in mammals.